2022
DOI: 10.1038/s41467-022-33824-6
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbe Bacteroides fragilis ameliorates renal fibrosis in mice

Abstract: Renal fibrosis is an inevitable outcome of various manifestations of progressive chronic kidney diseases (CKD). The need for efficacious treatment regimen against renal fibrosis can therefore not be overemphasized. Here we show a novel protective role of Bacteroides fragilis (B. fragilis) in renal fibrosis in mice. We demonstrate decreased abundance of B. fragilis in the feces of CKD patients and unilateral ureteral obstruction (UUO) mice. Oral administration of live B. fragilis attenuates renal fibrosis in UU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…F. lycii could increase B. fragilis to promote the expression of 1,5-anhydroglucitol (1,5-AG) , upregulate the Nuclear factor erythroid 2-related factor 2 (Nrf2)/ Recombinant Kelch Like ECH Associated Protein 1/(Keap1) pathway, downregulate the TGF-β/Smad pathway, inhibit renal fibrosis, and improve inflammation and intestinal injury. [60] CONCLUSION AND PROSPECT This literature review revealed that the gut microbiota may explain the property theory of TCM from a new perspective. At the genus level, Turicibacter, Parabacteroides, Dubosiella, Bifidobacterium, Bacteroides, Lactobacillus, Oscillospira, and Prevotella were upregulated, whereas Parasutterella, Mucispirillum, LachnoClostridium, Escherichia, Enterococcus, Butyricicoccus, Clostridiales, Blautia, Desulfovibrio, and Oscillibacter were downregulated.…”
Section: Liver Injurymentioning
confidence: 96%
See 1 more Smart Citation
“…F. lycii could increase B. fragilis to promote the expression of 1,5-anhydroglucitol (1,5-AG) , upregulate the Nuclear factor erythroid 2-related factor 2 (Nrf2)/ Recombinant Kelch Like ECH Associated Protein 1/(Keap1) pathway, downregulate the TGF-β/Smad pathway, inhibit renal fibrosis, and improve inflammation and intestinal injury. [60] CONCLUSION AND PROSPECT This literature review revealed that the gut microbiota may explain the property theory of TCM from a new perspective. At the genus level, Turicibacter, Parabacteroides, Dubosiella, Bifidobacterium, Bacteroides, Lactobacillus, Oscillospira, and Prevotella were upregulated, whereas Parasutterella, Mucispirillum, LachnoClostridium, Escherichia, Enterococcus, Butyricicoccus, Clostridiales, Blautia, Desulfovibrio, and Oscillibacter were downregulated.…”
Section: Liver Injurymentioning
confidence: 96%
“…[61] Moreover, Bifidobacterium and Lactobacillus were increased by Dioscoreae Rhizoma , F. lycii , and Poria and were negatively correlated with endotoxin production. [60] Thus, MS-TCMs can suppress endotoxin production by regulating the gut microbiota.…”
Section: Ms-tcms Treat Several Diseases Via the Gut Microbiota And It...mentioning
confidence: 99%
“…154 Zhou et al found that Bacteroides fragilis ameliorated renal fibrosis by decreasing LPS and increasing 1,5-AG levels in mice. 155 Hosomi et al administered Blautia wexlerae orally to mice and confirmed that the strain was sufficient to reduce obesity and alleviate type II diabetes. 120 Huber-Ruano et al found that Odoribacter laneus could improve host glucose tolerance and obesity-associated inflammation by depleting succinate in obese mice.…”
Section: Upgrading Of “Bacteria–drug Combination”mentioning
confidence: 99%
“…Zhou and coworkers 2 examined and established a causative relationship between the gut microbiota Bacteriodes fragilis ( B. fragilis ) and the progression of renal fibrosis. First, in 2 independent cohorts of CKD patients in China, the authors established that fecal B. fragilis correlated negatively with the stage of CKD assessed by serum BUN and creatinine.…”
Section: The Gut Microbe Bacteriodes Fragilis Ameliorates Renal Fibro...mentioning
confidence: 99%